Pelaksanaan pemberian bantuan sosial kepada korban bencana kebakaran di Desa Naru Kecamatan Sape Kabupaten Bima NTB - Zahratul Hayati; Nurul Qamarya; Susanti; Neti Sulami (ARKA INSTITUTE, 2022)
On October 10, 2021, a catastrophic fire hit Naru Village, Sape District, Bima Regency, West Nusa Tenggara. Hundreds of people had to be evacuated because their houses were razed to the ground. The fire devoured 63 houses consisting of 71 families (241 people lost their homes), the survivorswere still forced to live in refugee camps built by the army. This disaster occurred in the midst of the Covid-19 pandemic which has had a negative impact on economic conditions and public health. In order to ease the burden on the victims, the Surya Mandiri Midwifery Academy Bima initiated a community service program consisting of a fundraising campaign, raising funds from the community and collaborating with the Surya Mandiri Bima Midwifery Academy of Research and Community Service. This program is expected to raise awareness about the importance of providing assistance to disaster victims.